An integrated data collection system for line transect surveys - Gillespie, Douglas; Leaper, Russell; Gordon, Jonathan; Macleod, Kelly (J. Cetacean Res. Manage., 2023)
A computer based system for the collection of line transect survey data is described. The primary goals of the system were to measure (rather than estimate) distances and angles wherever possible, to provide accurate time-stamps for surfacing events as an aid to duplicate identification and to facilitate accurate data collection by using computers to automate data collection wherever possible. Distance and angle measurements were made using established photogrammetric techniques. Collection of photogrammetric data from video was automated and included a system of data buffering so that several seconds of data prior to each observer sighting could be captured. An additional goal of the system was to eliminate the need for post-cruise data entry and validation through the use of on-board data validation software. The system was successfully used during the 2005 SCANS-II and the 2007 CODA surveys.